Insights on Luminescent Micro- and Nanospheres of Infinite Coordination Polymers - Arroyos, Guilherme [UNESP]; da Silva, Caroline M. [UNESP]; Theodoroviez, Lucas B. [UNESP]; Campanella, Jonatas E. M. [UNESP]; Frem, Regina C. G. [UNESP] (Wiley, 2022)
Coordination polymers have been extensively studied in recent years. Some of these materials can exhibit several properties such as permanent porosity, high surface area, thermostability and light emission, as well as open sites for chemical functionalization. Concerning the fact that this kind of compounds are usually solids, the size and morphology of the particles are important parameters when an application is desired. Inside this context, there is a subclass of coordination polymers, named infinite coordination polymers (ICPs), which auto-organize as micro- or nanoparticles with low crystallinity. Specifically, the particles exhibiting spherical shapes and reduced sizes can be better dispersed, enter cells much easier than bulk crystals and be converted to inorganic materials by topotactic transformation. Luminescent ICPs, in particular, can find applications in several areas, such as sensing probes, light-emitting devices and bioimaging. In this review, we present the state-of-the-art of ICP-based spherical particles, including the growth mechanisms, some applications for luminescent ICPs and the challenges to overcome in future commercial usage of these materials.